PAT-4 Histopathological Study of Mice (Mus musculus) Digestive Organs Treated with Alkali pH Water - Sri Estuningsih; Vetnizah Juniantito; Yenny Rakhmawati (Hemera Zoa, 2018)
Water is an important part of the body. As much as 50-60% of an adult's body weight consists of water. Water functions in the body include as a means of transporting substances, regulating body temperature, regulating body pH, forming body structures, solvents for the body's chemical reactions, and helping the body's mechanical functions, such as lubrication (Insel et al. 2004; Asamadi 2008). In the event of water deficiency, the body will become dehydrated which able to cause cell death to individual death (Stanfield and Hui 2008). Recently, there are alkaline pH drinking water products that are commercially popular that have pH around 8-10 (alkaline water). Some parties claim that alkaline water can help neutralize the level of acidity (pH) of blood due to free radicals, while also having micro cluster technology that can increase oxygen solubility. According to Shirahata et al. (2012) alkaline water is beneficial for health because it can suppress oxidative stress.This study aims to know the effect of alkaline pH drinking water reviewed through histopathological studies of the digestive organs of mice (stomach, intestine, and pancreatic exocrine glands).